Stakeholder Capability Enhancement as a Path to Promote Human Dignity and Cooperative Advantage - Westermann-Behaylo, Michelle K. (Business ethics quarterly, 2016)
Promoting dignity is at the heart of the human capability approach to development. We introduce the concept of stakeholder capability enhancement, beginning with a discussion of the capability approach to development proposed by Sen (1985) and further advanced by Nussbaum (1990) to incorporate notions of dignity. Thereafter follows a review of the literature on value creation stakeholder management and convergent stakeholder theory (Freeman, 1984; Freeman, Harrison, Wicks, Palmer, & DeColle, 2010; Harrison & Wicks, 2013; Jones & Wicks, 1999), as the foundation for our concept of stakeholder capability enhancement. The remainder of this article develops a model that integrates stakeholder management with the human capability approach to detail the cooperative advantage that accrues to business and its stakeholders, as well as the gains in social wellbeing and dignity, when stakeholder capability enhancement becomes a common enterprise strategy. The model also explores the risks and boundary conditions firms face when seeking to profit from stakeholder capability tradeoffs. In explaining the model, we explore normative responsibilities and consequences with regard to human capabilities and dignity. We conclude with implications for future research.